Tarifa y su relación con los ingresos tributarios recaudados del impuesto al consumo de bolsas de plástico a nivel nacional periodo 2019-2023 - Tang Vela, Maricielo (2025)
This research addresses the issue of excessive plastic bag usage in Peru, which poses significant environmental impacts and socioeconomic costs. In 2019, the Plastic Bag Consumption Tax (ICBP) was implemented with an annually increasing rate as a policy instrument aimed at discouraging plastic bag use and contributing to environmental conservation. The main objective of the study was to determine the relationship between the ICBP rate and national tax revenue collected between 2019 and 2023. The methodology followed a quantitative approach with a non-experimental, correlational design, analyzing tax collection data published by SUNAT and the provisions of Law No. 30884, considering annual variations in both the tax rate and revenue. The results showed a significant increase in revenue during the first year of implementation, reflecting higher demand for taxed plastic bags. However, a downward trend was observed in subsequent years. It was also identified that the regions of Lima, Loreto, and San Martín recorded the highest levels of tax collection, ranking first, second, and third, respectively. A negative and statistically significant relationship was found between the increase in the tax rate and the revenue collected, with a Spearman correlation coefficient of -0.628 and a p-value below 0.001. The findings suggest that as the tax rate increases, both revenue and plastic bag consumption decrease, highlighting that the ICBP's extrafiscal objective prevails over its revenue-generating role, ultimately contributing to more responsible plastic bag usage.